IMPROVING THE TECHNOLOGY FOR THE DEVELOPMENT OF SPIRITUAL COMPETENCE OF FUTURE TEACHERS - Mamajonov O‘tkirbek Tojiddinovich (Scholars Digest Publishing, 2024)
The development of spiritual competence in future teachers is essential for fostering a nurturing and morally grounded educational environment. This article explores various methodologies, including theoretical knowledge, reflective practices, experiential learning, mentorship, and technology, to enhance spiritual competence in teacher education programs. By integrating these approaches, teacher education programs can provide future teachers with the tools they need to develop their values, ethical understanding, and emotional intelligence. Case studies and examples highlight successful strategies for integrating spiritual competence into teacher education programs, while addressing challenges such as diversity of beliefs and values and resistance to the concept of spirituality in education. Ultimately, prioritizing the development of spiritual competence in future teachers contributes to the creation of a positive and inclusive learning environment, where students are inspired to develop their own values, empathy, and sense of purpose.
Keywords: Spiritual competence, teacher education, values education, ethical understanding, emotional intelligence, reflective practices, experiential learning.